2005
DOI: 10.1128/aem.71.12.8016-8023.2005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Transcriptomic Adaptation of Lactococcus lactis subsp. lactis Biovar diacetylactis in Response to Autoacidification and Temperature Downshift in Skim Milk

Abstract: For the first time, a combined genome-wide transcriptome and metabolic analysis was performed with a dairy Lactococcus lactis subsp. lactis biovar diacetylactis strain under dynamic conditions similar to the conditions encountered during the cheese-making process. A culture was grown in skim milk in an anaerobic environment without pH regulation and with a controlled temperature downshift. Fermentation kinetics, as well as central metabolism enzyme activities, were determined throughout the culture. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
1
50
2
Order By: Relevance
“…Enzymes encoded by these genes reportedly contribute to raising internal pH in acidification conditions by liberation of NH 3 and are induced by acid stress (8), (47). These genes are reportedly downregulated in the presence of O 2 in different bacterial species (e.g., see references 16 and 26).…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes encoded by these genes reportedly contribute to raising internal pH in acidification conditions by liberation of NH 3 and are induced by acid stress (8), (47). These genes are reportedly downregulated in the presence of O 2 in different bacterial species (e.g., see references 16 and 26).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the diminished growth rate, whatever the cause of the slowing down, has large implications for global gene expression, affecting functions such as amino acid transporters, sugar metabolism, large and small ribosomal subunits, etc. (30,31). On the other hand, it is expected that very few genes will show variation of expression during exponential growth phases in which specific rates are comparable.…”
Section: Discussionmentioning
confidence: 99%
“…lactis is considered a model lactic acid bacterium, encountered extensively in numerous food fermentation processes, particularly in cheese production, industrial processes, and natural ecosystems. DNA arrays for L. lactis strain IL-1403, the first lactococcal strain to be sequenced (6), have recently been used for transcriptome analysis of L. lactis pure cultures (4,19,30,31). However, in most cases, L. lactis lives together with multiple microorganisms such as lactobacilli, corynebacteria, and yeasts (7,11,24,26,28,33,35).…”
mentioning
confidence: 99%
“…A number of studies have appeared that describe successful transcriptome or proteome analyses on samples from fermented substrates and even from highly complex materials such as fecal samples (81,178). Most studies of dairy fermentations use skim milk, in which the precipitation of casein may be prevented by pretreatment with sodium citrate (126,139). These studies have revealed several previously undescribed metabolic adaptations upon growth in milk, such as the induction of pyruvate-formate lyase in S. thermophilus that may serve as the supply of formate required for the biosynthesis of purine bases or other anabolic processes (37) (Fig.…”
Section: Genomics Approaches For Mixed-culture Researchmentioning
confidence: 99%